The Ecumenical role played by the church in promoting peace in Zimbabwe: Case of the Ecumenical Peace Observation Initiative. - Bobo, Tendayi (Midlands State University, 2017)
The research sought to assess the Ecumenical role of the Church in promoting Peace using the Ecumenical Peace Observation Initiative in Zimbabwe as a case study. In a qualitative outlook, the study critically unpacks the trends and dynamics of the nature of conflicts that have occurred in Zimbabwe at a national scale, post independence. The research then gives a detailed outline on the role of the Church in Peacebuilding in Zimbabwe in general as a means of addressing the conflicts identified. Zooming in, the study went on to analyse the joint initiatives of the Church implemented under the EPOIZ project in a bid to promote peace. Successes of the initiative were identified as well as challenges. In addressing the identified challenges, the study offers recommendations to strengthen the EPOIZ joint effort of the Church in Peacebuilding. In summing up this research based on all these discussions, a conclusion was given.